The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1097/01.ta.0000244384.85267.c5
|View full text |Cite
|
Sign up to set email alerts
|

Prehospital Prediction of the Severity of Blunt Anatomic Injury

Abstract: Paramedics were unable to reliably identify severe injury to individual body regions. Sensitivity of paramedic judgment of major trauma status was high. Assessment of the severity of injury to individual body regions did not appear to improve accuracy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 37 publications
2
40
0
1
Order By: Relevance
“…Two prospective observational studies demonstrated that paramedics can apply standing orders for a variety of medical and trauma-related complaints with acceptably low error rates and few adverse outcomes. 41,42 Mulholland et al demonstrated that paramedics could independently and reliably identify patients with life-threatening injuries, lessening the concern for undertriage for the critically ill. 35 A retrospective review of triage appropriateness by Lubin et al concluded that paramedics and community emergency physicians have similar proficiency at identifying cases appropriate for transfer to a level I trauma center. 43 However, a prospective observational study by Champion et al suggested paramedics might have a tendency to overtriage, and that online medical direction (OLMD) might reduce the overtriage rates by up to 50% in low-severity cases.…”
Section: Online Medical Controlmentioning
confidence: 99%
See 4 more Smart Citations
“…Two prospective observational studies demonstrated that paramedics can apply standing orders for a variety of medical and trauma-related complaints with acceptably low error rates and few adverse outcomes. 41,42 Mulholland et al demonstrated that paramedics could independently and reliably identify patients with life-threatening injuries, lessening the concern for undertriage for the critically ill. 35 A retrospective review of triage appropriateness by Lubin et al concluded that paramedics and community emergency physicians have similar proficiency at identifying cases appropriate for transfer to a level I trauma center. 43 However, a prospective observational study by Champion et al suggested paramedics might have a tendency to overtriage, and that online medical direction (OLMD) might reduce the overtriage rates by up to 50% in low-severity cases.…”
Section: Online Medical Controlmentioning
confidence: 99%
“…10,11 One recent analysis determined that the costs associated with trauma care and overtriage would decrease substantially if the CDC Guidelines for the Field Triage of Injured Patients were consistently applied.…”
Section: How Will This Ebg Improve Hems Triage?mentioning
confidence: 99%
See 3 more Smart Citations